Protective role of Cecropin AD against LPS-induced intestinal mucosal injury in chickens - Zhi, Yan; Li, Tingyu; Li, Yaxuan; Zhang, Tao; Du, Mengze; Zhang, Qian; Wang, Xiangdong; Hu, Ge (Frontiers in Immunology, 2023)
Introduction Cecropin AD (CAD), a renowned antimicrobial peptide, has shown promising potential in treating various bacterial infections. This study investigates the protective effects of CAD against lipopolysaccharide (LPS)-induced intestinal adversities in chickens. Methods Sixty SPF-grade chicks were divided into groups and exposed to different dosages of CAD, followed by LPS administration. The study assessed the impact of CAD on intestinal mucosal injury markers, oxidative stress, and inflammation. Results LPS significantly increased Diamine oxidase (DAO) and D-lactate (D-LA) levels, both indicators of intestinal mucosal injury. CAD treatment substantially attenuated these elevations, particularly at higher dosages. Additionally, CAD markedly reduced oxidative stress in intestinal tissues, as shown by normalized antioxidant levels and decreased reactive oxygen species. Histological analysis supported these findings, showing better-preserved villi structures in CAD-treated groups. Furthermore, CAD significantly reduced IL-6 and IL-8 expression post-LPS stimulation and effectively regulated the NLRP3 inflammasome pathway, decreasing associated factors like NLRP3, Caspase-1, IL-1b, and IL-18. Discussion The study demonstrates CAD's therapeutic potential in alleviating LPS-induced intestinal injuries. The protective effects are primarily attributed to its anti-inflammatory and antioxidative actions and modulation of the NLRP3 inflammasome pathway.